2022
DOI: 10.3389/fpsyg.2022.886344
|View full text |Cite
|
Sign up to set email alerts
|

Academic Stress and Mental Well-Being in College Students: Correlations, Affected Groups, and COVID-19

Abstract: Academic stress may be the single most dominant stress factor that affects the mental well-being of college students. Some groups of students may experience more stress than others, and the coronavirus disease 19 (COVID-19) pandemic could further complicate the stress response. We surveyed 843 college students and evaluated whether academic stress levels affected their mental health, and if so, whether there were specific vulnerable groups by gender, race/ethnicity, year of study, and reaction to the pandemic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 102 publications
1
32
0
1
Order By: Relevance
“…Stress has been reported as the foremost barrier to academic success (Benson et al, 2021). Students already have a higher level of stress than other populations (Eskin et al, 2016), and long-term college disruptions resulting from the COVID-19 pandemic have further increased that level of stress (Barbayannis et al 2022, Son et al 2020. Clabaugh et al (2021) found that in addition to the emotional impact of COVID-19, students also experience increased stress from an unfamiliar online learning environment.…”
Section: Academic Successmentioning
confidence: 99%
“…Stress has been reported as the foremost barrier to academic success (Benson et al, 2021). Students already have a higher level of stress than other populations (Eskin et al, 2016), and long-term college disruptions resulting from the COVID-19 pandemic have further increased that level of stress (Barbayannis et al 2022, Son et al 2020. Clabaugh et al (2021) found that in addition to the emotional impact of COVID-19, students also experience increased stress from an unfamiliar online learning environment.…”
Section: Academic Successmentioning
confidence: 99%
“…For example, a survey of university students in the UK indicated that loneliness, academic stressors, psychosocial issues, and a sense of coherence were the most potent predictors of mental wellbeing [16]. Another study in the USA found that academic stress led to the poor mental wellbeing of college students, particularly white and South Asian students, and the situation worsened further during COVID-19 [17]. In addition to the academic workload through emergency online learning, with growing academic uncertainty, increased sedentary behavior together with household responsibilities, particularly during financial hardship, may lead to potentially stressful life experiences and may increase the susceptibility to growing depression and anxiety among young adults [6,[18][19][20], including early married adolescents [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although the reasons leading to mental health issues among young adults during the pandemic are relatively well documented in Bangladesh [2][3][4][5][6][7][8][9] and elsewhere [10][11][12]19,20,22]; to the best of our knowledge, there is a shortage of empirical studies tracing back the reasons for mental health problems in general, particularly the individualized issues that are causing psychological problems and disrupting their lives [19]. Studies conducted in other countries have identified some predictors that may have negatively impacted young individuals' mental conditions [13][14][15][16][17][18]. Hence, the current study aims to explore the underlying causes of mental disorders among young adults in Bangladesh in order to advocate timely solutions for young adults experiencing mental health problems to assure uninterrupted educational progress and to minimize negative academic and psychosocial outcomes through institutional interventions [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological and emotional demands are the core components of the JD-R model of burnout, which are linked with strain and exhaustion [ 30 ]. In higher education, anxiety and depression have been proven to cause harmful emotional load [ 31 , 32 ]. Among resources, perceived possibility of personal growth and development, control, information, feedback, and support of lecturers are included as important components of the JD-R model [ 30 ].…”
Section: Introductionmentioning
confidence: 99%